2004
DOI: 10.1007/s00540-003-0225-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body temperature during profound hypothermic cardiopulmonary bypass in adult patients undergoing aortic arch reconstruction

Abstract: During induction of profound hypothermia and its reversal on total CPB with the heart in situ, a PA catheter thermistor, presumably because of its placement immediately behind the superior vena cava, would provide a reliable measure of the mixed venous blood temperature. During stabilized profound hypothermia, PAT, NPT, and FHT, but not UBT, serve as a reliable index of core temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Using the latter device, the zero-heat-flow temperature lagged behind both nasopharyngeal and PA temperatures during cooling and rewarming phases of CPB. 31,32 On the other hand, the difference may have been due to deeper hypothermia of less than 201C in the studies applying the Terumo device. In addition, the authors of the study presented here detected poor agreement between the SpotOn and nasopharyngeal temperatures at temperatures below 321C in the patient undergoing deeper hypothermia.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Using the latter device, the zero-heat-flow temperature lagged behind both nasopharyngeal and PA temperatures during cooling and rewarming phases of CPB. 31,32 On the other hand, the difference may have been due to deeper hypothermia of less than 201C in the studies applying the Terumo device. In addition, the authors of the study presented here detected poor agreement between the SpotOn and nasopharyngeal temperatures at temperatures below 321C in the patient undergoing deeper hypothermia.…”
Section: Discussionmentioning
confidence: 93%
“…In elective surgery a urinary bladder catheter is inserted only after the patient is anesthetized. Furthermore, the bladder temperature lags behind rapid changes 19,31 and might depend on the amount of urinary excretion. 34 In the study presented here, bladder temperature deviated from the primary core temperatures, considered to indicate heart and brain heat balance, at the beginning of the surgeries and during rapid changes during CPB.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder, rectum, and esophagus are proposed (1). There have been reports, mostly from elective surgical patients, that bladder and rectum sites do not reflect real-time temperature changes when hypothermia is induced, and that temperature changes in these sites lag behind core body temperature changes (5)(6)(7)(8)(9). So far, there is little information on which temperature measuring site is closest to temperature changes measured invasively in patients where hypothermia is induced after cardiac arrest (5,10).…”
Section: Introductionmentioning
confidence: 97%
“…Akata, et al have, furthermore, demonstrated that pulmonary artery temperatures closely reflect changes in brain temperatures, but nasopharyngeal/oesophageal measurements could not be considered as a reliable index of brain temperature, at all, during rapid induction of moderate/deep hypothermia. 36 Our study has some important limitations. It is an observational, retrospective study without randomisation and presents preliminary experience with a small number of patients.…”
Section: Discussionmentioning
confidence: 90%